Inflammasome and Its Therapeutic Targeting in Rheumatoid Arthritis - Jiang, Qi; Wang, Xin; Huang, Enyu; Wang, Qiao; Wen, Chengping; Yang, Guocan; Lu, Liwei; Cui, Dawei (Frontiers in Immunology, 2022)
Inflammasome is a cytoplasmic multiprotein complex that facilitates the clearance of exogenous microorganisms or the recognition of endogenous danger signals, which is critically involved in innate inflammatory response. Excessive or abnormal activation of inflammasomes has been shown to contribute to the development of various diseases including autoimmune diseases, neurodegenerative changes, and cancers. Rheumatoid arthritis (RA) is a chronic and complex autoimmune disease, in which inflammasome activation plays a pivotal role in immune dysregulation and joint inflammation. This review summarizes recent findings on inflammasome activation and its effector mechanisms in the pathogenesis of RA and potential development of therapeutic targeting of inflammasome for the immunotherapy of RA.